Respostas

2014-05-21T14:50:31-03:00
No conjunto IR, o solução da equação X(ao quadrado)/3 - 3-X(ao quadrado)/6 = 1/2

   x²/3 -3 - x²/6 = 1/2

   x²             x²         1
------ - 3     - -----   =  ------
   3              6           2       mmc de 3,6 ,2 | 2
                                                     3 ,3, 1| 3  
                                                      1,1  1/       2x3 = 6
2x² - 18   -  x²     = 3
--------------------------------------
                6.

2x² - 18 - x² = 3

2x² - x² - 18 = 3

x²  - 18 = 3
x² = 3 + 18
x² = 21

x = - + 
√21

x = - 
√21

x = + 
√21